Disanthus ovatifolius (Hamamelidaceae), a new species from northwestern Vietnam - Averyanov, Leonid V.; Endress, Peter K.; Quang, Bui Hong; Nguyen, Khang Sinh; Nguyen, Dzu Van (Phytotaxa, 2017)
Disanthus ovatifolius discovered in northwestern Vietnam is described as a new species of Hamamelidaceae, subfamily Disanthoideae. The new species belongs to the genus Disanthus, which was represented only by the type species of the genus, D. cercidifolius, until now. The new species differs from its congener in a series of morphological characters, such as the evergreen narrowly ovate leaves and cornute fruits. Detailed analytical color plate and ink drawing are provided for the new species along with data on its ecology, phenology and distribution. Similar plants were introduced into European horticulture under the invalid name Uocodendron whartonii hort. since 2006.